Optimizing the Use of Physics KITs that are integrated with the Scientific Context and Its Impact for Physics Teachers - Renol Afrizon; Hidayati Hidayati; Letmi Dwiridal; Najmil Khaira (Jurnal Penelitian Pendidikan IPA, 2021)
The background of this research is the lack of competence of physics teachers in using physics KIT. This research was conducted with the hope that there will be an increase in the competence of senior high school physics teachers in West Pasaman in using the physics KIT. This research was conducted with a quasi-experimental design and one group pretest-posttest. This study has a population of all physics teachers who join physics teachers group in West Pasaman Regency. The sample was taken by using simple random sampling technique, selecting 22 teachers as representatives of the physics teachers group in West Pasaman Regency. The results showed an increase in teachers' competence in using the physics KIT after mentoring the use of the physics KIT. The increase in teacher competence can be described through the value of again, the N-gain value obtained is 0.33 (moderate). This means that the teacher's competence in using the physics KIT can increase after mentoring the use of the physics KIT.